Banks in Space: Does Distance Really Affect Cross-Border Banking? - Katja Neugebauer (European Regional Science Association (ERSA), 2011)
During the last years, gravity equations have leapt from the trade literature over into the literature on financial markets. Martin and Rey (2004) were the first to provide a theoretical model for cross-border asset trade, yielding a structural gravity equation that could be tested empirically. In this paper, I use a gravity model to evaluate factors that affect cross-border banking. Furthermore, I extend the baseline model to allow for third-country effects, which have been shown to matter for international trade, using spatial econometric techniques. I try to answer the following question: First, is there a spatial dimension in cross-border banking? Second, if so, has it changed over time, and third, what happens if this spatial dimension is ignored? I use bilateral data on cross-border banking assets for 15 countries, and I estimate cross-section regressions for each year. I find strong evidence for a spatial dimension in cross-border banking. Furthermore, the direct effect of distance decreases significantly when applying spatial econometric techniques.
Keywords: 330